Theoretical and Therapeutic Implications of the Spasticity-Plus Syndrome Model in Multiple Sclerosis - Bruno, Antonio; Dolcetti, Ettore; Centonze, Diego (Frontiers in Neurology, 2022)
In multiple sclerosis (MS) patients, a typical pattern of muscle tone alteration, known as spasticity, is frequently observed in combination with other signs or symptoms such as spasms, cramps, pain, bladder dysfunction, sleep disturbances, fatigue, tremor. Recently, the concept of Spasticity Plus Syndrome (SPS) has been proposed to take into account the frequent coexistence of all these complaints in MS patients, and a common pathophysiological basis for this putative new clinical entity has been proposed. Muscle tone, sleep, bladder function and the pain pathway are controlled by cannabinoid CB1 (CB1R) and CB2 receptors (CB2R), that are particularly enriched in the brainstem. Axons with smaller diameters are particularly susceptible to conduction block and to the irritative, ephaptic, consequences of demyelination, and their involvement in the demyelination process caused by MS in the brainstem might underlie the various clinical manifestations of SPS. The adoption of SPS in clinical practice could be useful to improve symptomatic treatments in a significant proportion of MS patients, possibly limiting the adverse events produced by polypharmacotherapy.